Who Owns the Media? - Djankov, Simeon; McLeish, Caralee; Nenova, Tatiana; Shleifer, Andrei (World Bank, Washington, DC, 2014)
The authors examine patterns of media ownership in 97 countries around the world. They find that almost universally the largest media firms are controlled by the government or by private families. Government ownership is more pervasive in broadcasting than in the printed media. Government ownership is generally associated with less press freedom, fewer political and economic rights, inferior governance, and, most conspicuously, inferior social outcomes in education and health. The adverse effects of government ownership on political and economic freedom are stronger for newspapers than for television. The adverse effects of government ownership of the media do not appear to be restricted solely to instances of government monopoly. The authors present a range of evidence on the adverse consequences of state ownership of the media. State ownership of the media is often argued to be justified on behalf of the social needs of the disadvantaged. But if their findings are correct, increasing private ownership of the media--through privatization or by encouraging the entry of privately owned media--can advance a variety of political and economic goals, especially those of meeting the social needs of the poor.